Climate governance effects on carbon disclosure and performance. Issue 2 (March 2020) - Bui, Binh; Houqe, Muhammad Nurul; Zaman, Mahbub
Abstract: Integration of carbon oversight into board structures and processes has the potential to improve carbon performance and demonstrate accountability to stakeholders. However, it is not clear how climate governance affects carbon disclosure. Contributing to two strands of the literature, sustainability and governance issues, this paper examines the combined impact of climate governance on carbon disclosure. We find climate governance is associated with alignment between carbon disclosure and carbon performance. The results suggest that climate governance also reduces over-acclaiming of good performance via extensive disclosure, and low-polluters disclose more to differentiate themselves. Our findings highlight the importance of the frequency of reporting to the board and time horizon of carbon reporting for improving carbon disclosure and carbon performance. In contrast to traditional governance mechanisms, our results suggest climate governance better reflects firms' commitment to addressing sustainability issues and transparent reporting.